2016
DOI: 10.1055/s-0035-1569330
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes is Associated with Higher Trimethylamine N-oxide Plasma Levels

Abstract: Recent studies have revealed strong associations between systemic trimethylamine N-oxide (TMAO) levels, atherosclerosis and cardiovascular risk. In addition, plasma L-carnitine levels in patients with high TMAO concentrations predicted an increased risk for cardiovascular disease and incident major adverse cardiac events. The aim of the present study was to investigate the relation between TMAO and L-carnitine plasma levels and diabetes. Blood plasma samples were collected from 12 and 20 weeks old db/db mice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
173
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(189 citation statements)
references
References 30 publications
15
173
0
1
Order By: Relevance
“…Although previous studies have revealed that TMAO is linked to the development of diabetes in several animal models, no previous epidemiologic study, to our knowledge, has been designed specifically to examine the association between plasma TMAO and type 2 diabetes, with adjustment for other confounding factors. Plasma TMAO concentrations were found to be higher in patients with diabetes with or without cardiovascular comorbidities (5,20,24), but these studies did not investigate the associations between plasma TMAO and type 2 diabetes after adjustment for other confounding factors. Svingen and colleagues (18) found increased plasma TMAO in patients with type 2 diabetes, but no significant association was observed in their investigation.…”
Section: Discussionmentioning
confidence: 97%
“…Although previous studies have revealed that TMAO is linked to the development of diabetes in several animal models, no previous epidemiologic study, to our knowledge, has been designed specifically to examine the association between plasma TMAO and type 2 diabetes, with adjustment for other confounding factors. Plasma TMAO concentrations were found to be higher in patients with diabetes with or without cardiovascular comorbidities (5,20,24), but these studies did not investigate the associations between plasma TMAO and type 2 diabetes after adjustment for other confounding factors. Svingen and colleagues (18) found increased plasma TMAO in patients with type 2 diabetes, but no significant association was observed in their investigation.…”
Section: Discussionmentioning
confidence: 97%
“…This implies another metabolic pathway of indoxyl sulfate that is unique to this strain of mice. Another bacterial metabolite reported to have a negative effect on glucose metabolism (Dambrova et al, 2016) that is decreased by antibiotics in the plasma is TMAO, and this occurs with little effect on the cecal levels of the metabolite. On the other hand, propionate, which has been reported to have a favorable effect on insulin resistance (De Vadder et al, 2014), is also decreased in antibiotic-treated mice despite their improved insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…12 Several groups have observed that patients with diabetes tend to have higher TMAO and betaine levels when compared to healthy controls. 1719 Nevertheless, betaine levels may not directly convert to TMAO, and in the absence of elevated TMAO levels have yet to demonstrate any detrimental adverse consequences. 8 …”
Section: Tmao In Diabetes and Insulin Resistancementioning
confidence: 99%